Elección de sistema de explotación para el área de libre aprovechamiento de materiales de construcción, El Tablón GMZ; código 592157, sector El Tablón, cantón Zamora, provincia de Zamora Chinchipe. - Jiménez Rosales, Yulissa Raquel (2023)
This research work consists of a technical proposal of choice of the exploitation system for the free-use area about building materials, ‘El Tablón GMZ’; code 592157, located in the ‘El Tablon’area, canton of Zamora, province of Zamora Chinchipe, which has an area of 5 mining hectares, where the arid material to be exploited is the disaggregated granite. This belongs to the ‘Batholith of Zamora’, is mainly made up of quartz, plagioclase and feldspars, is mainly used for maintenance and filling of the final disposal cells of the landfill and for maintenance of the roads of the canton. The investigation work was developed in three stages: first, the pre-field stage, where the collection of bibliographic information of the area, legal documentation, etc. were carried out. Second, the field stage, where the information on site such as topography, geology, work cycles, etc. was corroborated. In function of using of the worksheets elaborated and the laboratory period, which allowed to know the geo-mechanical characteristics of the arid material mined in the area and its comparison with current regulations. Lastly, the office stage that consisted in the information processing, map making, multi-criteria analysis to define the exploitation system suitable for the area, calculations of machinery performance, identification of time used on each of the activities completed, in addition to the modeling of the exploitation system proposed, based on the raised formulas. The outcomes obtained allowed us to determine that the mining method is open pit and the optimal exploitation system for the area is quarry on hillside. through uphill banks, this considering the safety of the workers of ‘GAD Zamora’ who work in the mining area, in addition to the location of a stock zone inside the area, where its benefit lies in the reduction of work cycle times, greater performance of the machinery used and consequently increased daily production of the area of free use. Keywords: Exploitation system, material reserves, working cycles, geomechanical characteristics